Evaluation of dose-dependent hematotoxic effects of celastrol on human blood cells in vitro - Gayathri Hemant; Kurnegala Manikanta; Somanathapura K. NaveenKumar; Chandrashekar Tejas; Mysuru L. Sumedini; Kunthurumole S. Prashanth; Kabburahalli Sunitha; Kempaiah Kemparaju; Kesturu S. Girish (Toxicology Letters, 2026)

Quantum machine learning framework a novel approach for storm surge height estimation over the Bay of Bengal - A. Amasarao; P. Sunitha; K. Chandra Sekhar; K. A. Suneetha; B. Mmame (Stochastic Environmental Research and Risk Assessment, 2026)

Next-generation remediation tools: A review on cyclodextrin-based nanocomposites - Alka Rai; Amarpreet K. Bhatia; Sunitha B. Mathew; Sunita Sanwaria; Ajaya Kumar Singh; Ravin Jugade (Environmental Nanotechnology, Monitoring & Management, 2025)

Retraction notice to “Photocatalytic degradation of organic synthetic dyes and textile dyeing waste water by Al and F co-doped TiO2 nanoparticles” [Environ. Res. 206 (2022) 112492] - K. Ancy; M.R. Bindhu; Jeslin Sunitha Bai; Mansour K. Gatasheh; Ashraf Atef Hatamleh; S. Ilavenil (Environmental Research, 2025)

Chandra’s surface thermophysical experiment (ChaSTE) onboard Chandrayaan 3 Lander - Nizy Mathew; K. Durga Prasad; Dinakar Prasad Vajja; V. Aasik; Fazil Mohammad; P.P. Pramod; M. Satheesh Chandran; Kiran John Antony; M. Ram Prabhu; M.B. Dhanya; Manu V. Unnithan; Shiju G. Thomas; et al. (Advances in Space Research, 2025)

Role of surface and sub-surface ocean parameters on cyclonic storms over Arabian Sea in the recent decades - A. Amasarao; P. Sunitha; S. R. Rao; K. Chandra sekhar; B. Mmame (Natural Hazards, 2024)

A multi-electrode system for Pulsed Electric Field treatment chamber - Thomas Mohan; K.J. Suja; K. Sunitha (Journal of Food Engineering, 2024)

Fabrication of CuNPs Using Schiff Base Ligand and Their Catalytic Reduction of Pharmaceutical Drugs, Fluorescence Selective Detection of Cd2+, Antimicrobial, and Antioxidant Activities - G. Suneetha; Dasari Ayodhya; K. Srikanth; P. Sunitha Manjari (Journal of Fluorescence, 2024)

Delineation of groundwater potential zones using GIS and AHP techniques in Coimbatore district, South India - K. P. Kom; B. Gurugnanam; V. Sunitha (International Journal of Energy and Water Resources, 2024)

Unveiling the Radiative Electron-Hole Recombination of MoS2 Nanostructures at Extreme pH Conditions - Nayana K.; Sunitha A. P. (Journal of Fluorescence, 2024)

Assessment of CMIP6 model performance in simulating atmospheric aerosol and precipitation over Africa - B. Mmame; P. Sunitha; K. Samatha; S.R. Rao; P. Satish; A. Amasarao; K. Chandra Sekhar (Advances in Space Research, 2023)

Groundwater quality assessment using multivariate statistical approach and geospatial modelling around cement industrial corridor, South India - B. Suvarna; V. Sunitha; Y. Sudharshan Reddy; B. Muralidhara Reddy; A. K. Kadam; M. Ramakrishna Reddy (International Journal of Environmental Science and Technology, 2023)

Pollutant removal from cheese processing effluent using effective indigenous natural scavengers - B. Sowmiya Rajalakshmi; A. Annes silva fathima; B. Sunitha Jasmine; M. Vasanthy; C. Thamarai Selvi; Rajinikanth Rajagopal; Ramsha Khan; Ashraf Atef Hatamleh; Bassam Khalid Alnafisi; Mansour K. Gatasheh; Soon Woong Chang; Balasubramani Ravindran (Environmental Monitoring and Assessment, 2023)

Familial idiopathic intracranial hypertension: a unique and rare entity with dramatic response to weight reduction - Sachin Sureshbabu; Sunitha Mathew; Merisin Joseph; Sujith Janardhanan; Sudhir Peter; Sobhana Chindripu; Noufal Basheer; K. P. Abdurehiman (Acta Neurologica Belgica, 2022)

Yield Estimation of Cassava Using SIMCAS Model Over the Major Cassava Growing Regions in India - Divya K. Lekshmanan; Raji Pushpalatha; V. S. Santhosh Mithra; S. Sunitha; James George; M. Velmurugan; P. Ashok; N. V. Mhasker; K. D. Desai; R. Shiny; Gangadharan Byju (Agricultural Research, 2022)

Impact of climate change on the yield of tropical root and tuber crops vs. rice and potato in India - Raji Pushpalatha; VS Santhosh Mithra; S Sunitha; James Goerge; M Nedunchezhiyan; K Mamatha; P Ashok; Sheriful Alam; BK Saud; J Tarafdar; Surajit Mitra; Chandra Deo; et al. (Food Security, 2022)

Testing of Cassava (Manihot esculenta) Varieties for Climate Resilience Under Kerala (India) Conditions - Raji Pushpalatha; R. Shiny; Govindan Kutty; V. K. Dua; S. Sunitha; V. S. Santhosh Mithra; G. Byju (Agricultural Research, 2022)

ENIGMA + COINSTAC: Improving Findability, Accessibility, Interoperability, and Re-usability - Jessica A. Turner; Vince D. Calhoun; Paul M. Thompson; Neda Jahanshad; Christopher R. K. Ching; Sophia I. Thomopoulos; Eric Verner; Gregory P. Strauss; Anthony O. Ahmed; Matthew D. Turner; Sunitha Basodi; Judith M. Ford; et al. (Neuroinformatics, 2022)
The FAIR principles, as applied to clinical and neuroimaging data, reflect the goal of making research products F indable, A ccessible, I nteroperable, and R eusable. The use of the Collaborative Informatics and Neuroimaging Suite Toolkit for Anonymized Computation (COINSTAC) platform in the Enhancing Neuroimaging Genetics through Meta-Analysis (ENIGMA) consortium combines the technological approach of decentralized analyses with the sociological approach of sharing data. In addition, ENIGMA + COINSTAC provides a platform to facilitate the use of machine-actionable data objects. We first present how ENIGMA and COINSTAC support the FAIR principles, and then showcase their integration with a decentralized meta-analysis of sex differences in negative symptom severity in schizophrenia, and finally present ongoing activities and plans to advance FAIR principles in ENIGMA + COINSTAC. ENIGMA and COINSTAC currently represent efforts toward improved Access, Interoperability, and Reusability. We highlight additional improvements needed in these areas, as well as future connections to other resources for expanded Findability.

A new paradigm for short-range forecasting of severe weather over the Indian region - Soma Sen Roy; Pradeep Sharma; Bikram Sen; K. Sathi Devi; S. Sunitha Devi; Neetha K. Gopal; Naresh Kumar; Krishna Mishra; Shobhit Katyar; Surendra Pratap Singh; Shibin Balakrishnan; Charan Singh; et al. (Meteorology and Atmospheric Physics, 2021)

Protective effect of (+)–catechin against lipopolysaccharide-induced inflammatory response in RAW 264.7 cells through downregulation of NF-κB and p38 MAPK - M. A. Sunil; V. S. Sunitha; Prasanthkumar Santhakumaran; Mohind C. Mohan; Midhun Sebastian Jose; E. K. Radhakrishnan; Jyothis Mathew (Inflammopharmacology, 2021)

Role of enhanced synoptic activity and its interaction with intra-seasonal oscillations on the lower extended range prediction skill during 2015 monsoon season - S. Abhilash; R. Mandal; A. Dey; R. Phani; S. Joseph; R. Chattopadhyay; S. De; N. K. Agarwal; A. K. Sahai; S. Sunitha Devi; M. Rajeevan (Climate Dynamics, 2018)

LRP2 gene variants and their haplotypes strongly influence the risk of developing neural tube defects in the fetus: a family-triad study from South India - Rebekah Prasoona K.; Sunitha T.; Srinadh B.; Muni Kumari T.; Jyothy A. (Metabolic Brain Disease, 2018)

Occurrence and Antibiotic Susceptibility Testing of Vibrio cholerae from District Wayanad, Kerala, India - Ebin Baby Mathews; B. Sunil; N. Prejit; C. Sunanda; V. K. Vinod; Jess Vergis; K. Asha; R. Sunitha (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2018)

Gut physiology mediates a trade‐off between adaptation to malnutrition and susceptibility to food‐borne pathogens - Roshan K. Vijendravarma; Sunitha Narasimha; Sveta Chakrabarti; Aurelie Babin; Sylvain Kolly; Bruno Lemaitre; Tadeusz J. Kawecki (Ecology Letters, 2015)
The animal gut plays a central role in tackling two common ecological challenges, nutrient shortage and food‐borne parasites, the former by efficient digestion and nutrient absorption, the latter by acting as an immune organ and a barrier. It remains unknown whether these functions can be independently optimised by evolution, or whether they interfere with each other. We report that Drosophila melanogaster populations adapted during 160 generations of experimental evolution to chronic larval malnutrition became more susceptible to intestinal infection with the opportunistic bacterial pathogen Pseudomonas entomophila . However, they do not show suppressed immune response or higher bacterial loads. Rather, their increased susceptibility to P. entomophila is largely mediated by an elevated predisposition to loss of intestinal barrier integrity upon infection. These results may reflect a trade‐off between the efficiency of nutrient extraction from poor food and the protective function of the gut, in particular its tolerance to pathogen‐induced damage.

Viper venom-induced oxidative stress and activation of inflammatory cytokines: a therapeutic approach for overlooked issues of snakebite management - M. Sebastin Santhosh; M. Shanmuga Sundaram; K. Sunitha; K. Kemparaju; K. S. Girish (Inflammation Research, 2013)

An overview on genus garcinia: phytochemical and therapeutical aspects - M. Hemshekhar; K. Sunitha; M. Sebastin Santhosh; S. Devaraja; K. Kemparaju; B. S. Vishwanath; S. R. Niranjana; K. S. Girish (Phytochemistry Reviews, 2011)

Morphological and biochemical factors associated with resistance to Maruca vitrata (Lepidoptera: Pyralidae) in short-duration pigeonpea - V. Sunitha; G.V. Ranga Rao; K. Vijaya Lakshmi; K.B. Saxena; V. Rameshwar Rao; Y.V.R. Reddy (International Journal of Tropical Insect Science, 2008)

Synthesis of alkaline protease by catabolite repression- resistant Thermoactinomyces sp. E79 mutant - K. Sunitha; Young-Seo Park; Tae-Kwang Oh; Jung-Kee Lee (Biotechnology Letters, 1999)

Expression of thermostable alkaline protease gene from Thermoactinomyces sp. E79 in E. coli and heat activation of the gene product - Jung-Kee Lee; Young-Ok Kim; K. Sunitha; Tae-Kwang Oh (Biotechnology Letters, 1998)